Karakteristik Penataan Ruang dan Fasilitas Publik Pada Kampung Pulau Belimbing - Muhd. Arief Al Husaini (Prodi Arsitektur Universitas Matana, 2018)
The modernization of urban development should not lose the values of traditional principles and local wisdom. According to decentralization development strategic, in creating friendly city should be closely related to traditional inhabitation wisdom. Pulau Belimbing traditional neighborhood has practiced local wisdom values in planning and designing of public space and facilities for hundreds of years. The traditional kampong is developed with the characteristics of space fairness and equal accessibility to accommodate the needs of local tribes. The knowledge and application of such wisdom could help in the planning of friendly city development, especially in Malay land. The aim of this paper is to review the characteristic of public space and facilities planning in Pulau Belimbing traditional neighborhood. This research applies naturalistic paradigm with qualitative approach and diachronic reading as the tool of analysis. The study indicates that Pulau Belimbing traditional neighborhood has implemented the principles of friendly city in planning of public space and facilities. The tradition inhabitation wisdom can be model for the development of future city, especially in public spaces provision.